Contact-genetic linguistics: toward a contact-based theory of language change. (March 2015) - Operstein, Natalie
Abstract: This paper introduces a theory of language descent based on an interplay between inheritance and contact mechanisms of language transmission. The proposed approach emphasizes the alternation between periods of gradual and rapid change in the history of languages, with the assumption that during both types of periods, change is due to language contact, with a differing agency of change and a different predominant mode of transmission (to L1 or L2 learners). Rooted in the diachronic aspects of language change, and incorporating recent advances in sociolinguistic typology and the typology of language-contact phenomena, the theory also contributes to our understanding of the concept of genetic relatedness.